The Pengaruh Pemberian Kompres Dingin Perineum terhadap Intensitas Nyeri pada Ibu Postpartum Pervaginam dengan Episiotomi - Fatia Isna Rahmadhani; Sri Sumaryani; Endang Jumiati (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Perineal pain due to episiotomy is a common complaint experienced by postpartum mothers and can affect patient comfort, mobility, and recovery. Nonpharmacological pain management is needed to help reduce discomfort with minimal risk of side effects. Objective: This study aimed to determine the effectiveness of applying cold compresses using ice packs in reducing perineal pain intensity in postpartum mothers with episiotomy. Methods: The study used a descriptive case study design in three vaginal postpartum patients with episiotomy who were treated in the postpartum ward. The intervention involved applying cold compresses using ice packs to the perineal area for 10–15 minutes, as per nursing procedures. Pain was measured using the Numeric Rating Scale (NRS) before and after the intervention. Findings: The results showed a decrease in pain intensity in all patients after the application of cold compresses. Patient P1 experienced a decrease in pain score from 5 to 4, patient P2 from 6 to 5, and patient P3 from 5 to 4, with an average decrease of 1 point. Implications: Cold compresses using ice packs have the potential to be an effective non-pharmacological nursing intervention to help reduce perineal pain and improve the comfort of postpartum mothers with episiotomies during the care period.